Factors Improvement of Sustainable livelihoods from the Perspective of Local People, Case Study: Ardabil County - vakil heidari sarban; Alireza Abdpour (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this paper is to investigate the factors improvement of sustainable livelihoods from the perspective of local people of Ardabil County. First, factors affecting effectiveness improvement of sustainable livelihoods in the study area were identified from the perspective of local elites using semi-structured interviews. To achieve this goal, 35 residents of studied region were interviewed individually with college education and at least a bachelor's degree. In the second step of study, in order to understand and analyze rural communities' perspective of and their theoretical agreement degree with the results of the first step, 39 identified causes were the questionnaire design basis by Likert method. It can be said that studied population in this study consists of all villagers living in rural areas of Ardabil County in 2016 (N= 85053), among which 383 persons were selected as statistical sample using Cochran formula. In order to analyze the data, factor analysis model was used and the results of this model showed the most important factor improvement of sustainable livelihoods from the perspective of local people in studied region includes four components (entrepreneurship and fortification of economical infrastructures, support of demand- side and governmental interventional action, fortification of social capital and social empowerment and environmental management and fortification of physical infrastructures) that explained variance and the cumulative variance by the five factors 60.66. And finally, practical suggestions have been presented according to the results of the study.